Evolutionary relationships of the Tehuelche scallop Aequipecten tehuelchus (Bivalvia: Pectinidae) from the south-western Atlantic Ocean - Trovant, Berenice; Real, Luciano Esteban; Parma, Ana María; Orensanz, Jose Maria; Basso, Nestor Guillermo (Journal of the Marine Biological Association of the United Kingdom)
This study addresses aspects of the phylogenetic relationships of the commercial Tehuelche scallop, Aequipecten tehuelchus s.l. (Bivalvia: Pectinidae), from southern South America using molecular techniques. The Tehuelche scallop presents two different putative subspecies, A. t. tehuelchus and A. t. madrynensis, and a potentially related sympatric species, Flexopecten felipponei. The Tehuelche scallop is a very important component of ecosystems and is the target of artisanal fisheries in the northern Patagonian gulfs of Argentina. Despite its importance, the systematic relationships of these taxa have not been fully addressed. The main goal of this study is to place the Tehuelche scallop within a partial phylogenetic framework of the family Pectinidae. Scallops were sampled at 10 localities distributed along the south-western Atlantic Ocean. Phylogenetic reconstructions were carried out from two mitochondrial (12S rRNA and 16S rRNA) and two nuclear markers (28S rRNA and H3) using Bayesian, maximum likelihood and maximum parsimony analyses. Our phylogenetic analysis indicates that the two putative subspecies of the Tehuelche scallop together with F. felipponei form a monophyletic clade, without differentiating at the specific level. Observed differences would be the result of phenotypic plasticity, probably caused by environmental factors. However, further analysis using genes with faster evolution rate are needed to corroborate it. Our phylogenetic analysis resolved to Aequipecten as polyphyletic. The Tehuelche scallop has a basal position within the Argopecten group and we recommend that it should be transferred to this genus. The relationship between the hypotheses about the origin of the Tehuelche scallop implicit in the literature and our results are discussed. Fil: Trovant, Berenice. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Diversidad y Evolución Austral; Argentina Fil: Real, Luciano Esteban. Consejo ...